PENGARUH PERSEPSI DAN MOTIVASI TERHADAP MINAT MAHASISWA KONSENTRASI PERPAJAKAN PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MUSLIM INDONESIA - Fadli, Zul (Restitusi : Jurnal Riset Perpajakan, 2023)
This research aims to analyze: students' perceptions and motivation simultaneously regarding their interest in taxation concentration at the Faculty of Economics and Business, Indonesian Muslim University. This research is a type of quantitative research, with the research population being all final semester students taking the taxation concentration at the Faculty of Economics and Business, Indonesian Muslim University . The sampling technique used incidental sampling to obtain a sample size of 75 people. Data analysis techniques are descriptive analysis and multiple linear regression analysis. The results of this research show that: (1) perception has a positive and significant effect on the interest of students concentrating on taxation, (2) motivation has a positive and significant effect on the interest of students concentrating on taxation, (3) perception and motivation together have a positive and significant effect on interest students to choose a taxation concentration.